Development and characterization of microsatellite markers in Campomanesia adamantium, a native plant of the Cerrado ecoregions of South America - Crispim B.D.A. (2019)
© 2019 Crispim et al. Applications in Plant Sciences is published by Wiley Periodicals, Inc. on behalf of the Botanical Society of AmericaPremise: A novel set of nuclear microsatellite markers was developed and characterized for Campomanesia adamantium (Myrtaceae) and tested for cross-amplification in the related species C. sessiliflora. Methods and Results: Forty-one primer pairs were designed for simple sequence repeat loci, of which 36 successfully amplified and were polymorphic. The number of alleles ranged from two to 14, with an average of 8.14 alleles per locus. Additionally, cross-amplification was tested in C. sessiliflora; more than 55.5% of the microsatellite loci amplified, confirming the use of these microsatellite markers in a related species. Conclusions: We developed a set of microsatellite markers that will be useful for future studies of genetic diversity and population structure of C. adamantium and a closely related species, which will aid in future conservation efforts.